The phylogenetic relationships of Przevalski's Finch Urocynchramus pylzowi, the most ancient Tibetan endemic passerine known to date. (24th May 2016) - Päckert, Martin; Martens, Jochen; Sun, Yue‐Hua; Strutzenberger, Patrick
Abstract : Competing systematic hypotheses have placed the Tibetan endemic Przevalski's Finch Urocynchramus pylzowi either with the Old World buntings (Emberizidae) or with the cardueline finches (Fringillidae, Carduelinae). Recent studies based on limited genetic evidence instead suggest an isolated position within Passeroidea and advocate a separate family, Urocynchramidae, as had been suggested much earlier on the grounds of morphology. We provide a time‐calibrated multi‐locus phylogeny for Passeroidea including Przevalski's Finch based on three mitochondrial markers and three nuclear introns that placed U. pylzowi in a clade together with Estrildidae, Viduidae and Ploceidae. A sister group relationship of U. pylzowi and weavers (Ploceidae) was concordant among three multilocus reconstructions but received only poor support. Divergence time estimates inferred from a fossil/biogeographical molecular dating approach suggested a late Oligocene split of U. pylzowi from its closest relatives at roughly 25 million years ago, making this the oldest known Tibetan endemic passerine. In addition to the molecular data, behavioural peculiarities and egg coloration further strengthen an isolated placement of U. pylzowi .